Study on iNOS expression and levels of Malondialdehyde in the White Rat (Rattus norvegicus) Exposed with Aggregatibacter actinomycetemcomitans - Reviana Setin; Aulanni'am Aulanni'am; Chanif Mahdi (The Journal of Pure and Applied Chemistry Research, 2013)
Aggregatibacter actinomycetemcomitant (Aa) is gram-negative bacteria composed of lipopolysaccharides (LPS) in its outer membrane. This bacteria is normally found in dental plaque and periodontal pockets causing parotid gland damage when it is present in excess amounts. LPS is an endotoxin and a complex glycolipid composed of polysaccharides (hydrophilic) and lipid A (hydrophobic) which can induces Reactive Oxygen Species (ROS), and increase the levels of malonaldialdehyde (MDA) and tissue damage. The aims of this research are to find the expression of iNOS parotid gland cell and to determine levels of MDA using thiobarbituric acid (TBA) spectrophotometric test at 533 nm. The results showed a significantly difference (P<0.05) of MDA levels in control rats (3.135 ± 0.0436 ppm) and Aa rats (6.307 ± 0.0473 ppm). iNOS expression is confirmed by the brown spots formed on the parotid gland, affording the enhancements of iNOS expression in Aa rats and control rats of 2.292 ± 0.038 and 0.166 ± 0.003, respectively (P<0.05). Keywords       : Aggregatibacter actinomycetemcomitans, Reactive Oxygen Species, malondialdehyde, iNOS